2007
DOI: 10.1074/jbc.m611449200
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Binding and Calcium Influx Induce Distinct Ectodomain/γ-Secretase-processing Pathways of EphB2 Receptor

Abstract: Binding of EphB receptors to ephrinB ligands on the surface of adjacent cells initiates signaling cascades that regulate angiogenesis, axonal guidance, and neuronal plasticity. These functions require processing of EphB receptors and removal of EphB-ephrinB complexes from the cell surface, but the mechanisms involved are poorly understood. Here we show that the ectodomain of EphB2 receptor is released to extracellular space following cleavage after EphB2 residue 543. The remaining membrane-associated fragment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
133
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 50 publications
9
133
2
Order By: Relevance
“…This proposal is consistent with a report that regulated vesicular trafficking controls the formation of Pcdh-Pcdh contacts between neurons in a manner that requires the Pcdh ICDs (29). For the Notch receptor, endocytosis and γ-secretase cleavage are dependent on monoubiquitination, and sorting of Notch to the lysosome is dependent on the Nedd4 family of E3 ligases (31,40,(41)(42)(43). Processing of Pcdh may be regulated in a manner similar to that of Notch.…”
Section: Discussionsupporting
confidence: 77%
“…This proposal is consistent with a report that regulated vesicular trafficking controls the formation of Pcdh-Pcdh contacts between neurons in a manner that requires the Pcdh ICDs (29). For the Notch receptor, endocytosis and γ-secretase cleavage are dependent on monoubiquitination, and sorting of Notch to the lysosome is dependent on the Nedd4 family of E3 ligases (31,40,(41)(42)(43). Processing of Pcdh may be regulated in a manner similar to that of Notch.…”
Section: Discussionsupporting
confidence: 77%
“…Despite the transiency of Ca 2þ microdomains and despite the buffering of Ca 2þ by Ca 2þ -binding proteins such as calmodulin, 107 increased concentrations of Ca 2þ inside microdomains suffice for a local activation of calpains. While the cleavages of proteins by calpains are the chief proteolytic consequence of Ca 2þ transients, these fluxes are also capable of activating some secretases, [108][109][110] and caspases as well, in part through activation of the apoptosome and inflammasome. 111,112 Many, possibly most neurons contain activated caspases such as caspase-3 (an effector caspase) under conditions in which caspase activation and caspase-mediated protein cuts are relatively constrained and do not cause cell death.…”
Section: The Fragment Generation Hypothesismentioning
confidence: 99%
“…7C). Considering that it has been recently reported that RIP of the p75 neurotrophin receptor (18), EphB2 receptor (123), and Notch (124) occurs subsequent to endocytosis on the endosome, determining whether ␥-secretase-dependent proteolysis of IL-1R1 CTF occurs at the plasma membrane or endosome requires further experimentation. Highlighting the physiological importance of this model, we show that pharmacological inhibitors of ␥-secretase activity inhibit generation of IL-1R1-ICD and antagonize IL-1␤-induced JNK activation.…”
Section: Ps2mentioning
confidence: 99%